C87 THE SHORT–TERM PROGNOSTIC SIGNIFICANCE OF BASELINE TROPONIN LEVELS IN PATIENTS HOSPITALIZED FOR COVID–19. (18th May 2022) - Di Maio, F; Baldin, G; Todde, N; Volpi, N; Basan, L; Vannucci, V; Ruzittu, G; Pisanu, A; Seddone, S; Santoru, M; Delogu, G; Favuzzi, A; et al.
Abstract: Background: Troponin (TN) is the biomarker of choice for the detection of cardiomyocite injury. Elevation of TN has been noted in COVID–19 patients (pts), implicating myocardial injury as a possible pathogenic mechanism contributing to disease severity. Aim: To assess the in–hospital prognostic significance of baseline TN levels in COVID–19 pts. Methods. The data of 192 consecutive COVID–19 individuals (mean age 70±15 yrs, 54.6% males) hospitalized in a single institution were retrospectively analysed. According to the baseline TN–I levels (normal value up to 34 pg/ml), the whole population was divided into normal (Group A) and elevated (Group B) TN–I. Demographic parameters, clinical history, pharmacological treatments and laboratory data at the admission were evaluated. The length–of–stay, rate of orotracheal intubation, non–invasive ventilation and in–hospital mortality were considered as prognostic parameters. Results: One–hundred–fifty–seven pts belonged to Group A, while thirty–five pts to Group B. Group A pts were significantly younger (67±14 vs 79 ±12 yrs, p < 0.001). As expected, a better renal profile was observed in pts with normal TN–I levels (eGFR 82±25 ml/m' in Group A vs 48±30 ml/m' in Group B, p < 0.001). No differences were noted between the two groups in the prevalence of diabetes, previous CAD, hypertension, ACE/ARBs treatment. The length–of–stay was similar (21±11days in Group A vs 19±17 days in Group B, respectively, p=ns). Also, the need for orotracheal intubation (11.4% vs 11.5% p=ns) and non–invasive ventilation (26.8% vs 28.6%, p=ns), were not significantly different between Group A and Group B. However, the in–hospital mortality was considerably lower in pts with normal baseline TN–I, as compared to those with a definite level of cardiomyocyte damage (20/157 Group A pts, 12.7%, vs 15/35 Group B pts, 42.9%, p < 0.001). Conclusion: Our data demonstrate that high TN–I baseline level upon admission should be considered as a strong prognostic parameter in pts hospitalized for COVID–19. In our population, this observation seems not to be related to the different comorbidities, except for the renal function profile.